Exploring the impact of internet use on cognitive abilities in the older adults: evidence from the CHARLS 2020 database - Jiao, Haojin; Guo, Zehui; Sun, Jiafan; Wang, Ke; Yang, Jingqi (Frontiers in Public Health, 2025)
IntroductionThe rapid aging of the global population has increased the prevalence of cognitive impairments, presenting significant challenges for healthcare systems. This study examines the potential protective role of internet use against cognitive decline among older adults in China.MethodsUtilizing the China Health and Retirement Longitudinal Study (CHARLS 2020) data, this research analyzed a sample of 7,142 Chinese adults aged 60 and above. The study employed correlation analysis and hierarchical regression to explore the relationship between various dimensions of internet use and cognitive function.ResultsResults indicate a significant positive correlation between internet use and cognitive performance, suggesting that digital engagement may serve as a protective factor against cognitive decline. Additionally, the study reveals that socio-demographic factors such as age, education level, and urban or rural residency modulate this relationship.DiscussionThe findings underscore the importance of digital inclusivity for enhancing cognitive health among older adults. This study discusses the implications of increasing internet accessibility and provides recommendations for public policy to foster a digitally inclusive society that supports the cognitive health of the aging population.